The Inside of the Cup $1 (BVolume 02s - Churchill, Winston, 1871-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Inside of the Cup $1 (BVolume 02" by Winston Churchill is a novel published in 1913. John Hodder, a minister recruited to lead an affluent urban church, initially preaches to satisfy wealthy patrons who desire a Christianity that doesn't challenge corporate power or concentrated wealth. After befriending the powerful but lonely Eldon Parr, Hodder undergoes a spiritual crisis that transforms his ministry. He begins preaching Jesus's core message of loving and serving mankind, sparking fierce conflict within his congregation and igniting nationwide debate about Christianity's role in modern American life. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Inside_of_the_Cup
Release date is 2004-10-19
Produced by David Widger
Keywords: Christian life -- Fiction; Attitude change -- Fiction; Christian ethics -- Fiction; Conscience -- Religious aspects -- Fiction